Polimosfisme Lokus Mikrosatelit BM1329 dan Hubungannya dengan Calving Interval pada Sapi Bali - Merliana, Made Raysa; Wandia, I Nengah; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 2 No 2 (2014), 2014)
Bali cattle plays an important role in supplying beef in Indonesia because it has good quality, high fertilization and low fat percentage. The aim of this research was to characterize the Bali cattle genetic using molecular marker of microsatellite BM1329 and its relation with calving interval. The data was taken from 19 cattles that belong to UD Sari Laba, Bangli, Bali. The association between BM1329 marker and calving interval was analyzed using General Linear Models concept. The result showed that the duration of calving interval for the Bali cattle was 314 – 451 days. There were 4 alleles found in the locus of microsatellite BM1329. The alleles size varied from 144 to 150 bp, in which, the allele 146 had the highest frequency (71.05%). The observed heterozigosity (Ho) and the expected heterozigosity (He) and the PIC were 0.474, 0.478, and 0.435 respectively. The statistical analysis showed that microsatellite BM1329 has no assocition with the calving interval (P>0.05).
Keywords: Microsatellite BM1329, heterozigosity, calving interval, Bali cattle